SELF Q-SWITCHING OF A CW MODE-LOCKED ND-YLF LASER BY CAVITY LENGTH DETUNING - JHON, YM; KONG, HJ (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1993)
The cavity length of a CW mode-locked Nd: YLF laser is detuned to investigate its effect on the output of the laser. Negative detunings of 0.4 to 2.4 mum result in periodic modulations of the pulse envelope. Further negative detunings of 2.4 to 3.4 mum produce undamped regular spikings, that is, stable self Q switching behavior with mode-locked pulses of 30 approximately 47 ps pulsewidths, which are as short as those of plain mode locking without Q switching. Similar self Q switching behavior is also produced by positive detunings, but the stability is very poor.
Keywords: YAG-LASER; FREQUENCY